Representation of Leaders in the Media with Critical Discourse Analysis of Dedi Mulyadi's Policy - Dina Agustriani; Agus Hamdani (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2025)
This study analyzes the representation of policies and leadership image of West Java Governor Dedi Mulyadi in the news coverage from five national online media: Kompas.com, iNews.id, Tribunjabar.id, Detik.com, and RRI.co.id. The approach used is critical discourse analysis (CDA) based on Norman Fairclough's model, covering three dimensions: microstructural (text), mesostructural (production practices), and macrostructural (social context). The analysis reveals that affirmative diction choices and straightforward sentence structures are key strategies in constructing a positive image of Dedi Mulyadi. At the mesostructural level, all media tend to present information from a single source, namely government officials, without offering critical or opposing perspectives. On the macro level, the coverage reflects the power relations between the media and government institutions, where the media serves as a tool to shape public opinion that supports the narrative of development and single leadership. This study emphasizes the importance of media engagement in providing space for criticism and diverse voices in the reporting of public policies.